Comparative analysis of Erycibe schmidtii Craib and its potential substitutes based on metabolites and pharmacodynamic effect - Li, Ning; Ye, Chen-Yu; Hu, Jing; Qu, Tong; Lu, Wen-Jing; Cui, Xiao-Min; Liang, Chao; Chen, Zhi-Yong; Ren, Hui; Lai, Chang-Jiang-Sheng (Frontiers in Pharmacology, 2025)
BackgroundErycibe schmidtii Craib (Esc), a traditional treatment for rheumatoid arthritis (RA), faces resource scarcity, leading to the emergence of potential substitutes in the market. Although these potential substitutes have shown properties that alleviate RA-symptoms, their therapeutic equivalence to Esc still requires systematic validation.PurposeThis study aims to identify suitable potential substitutes for Esc and elucidate their therapeutic mechanisms for RA by conducting comparative analyses of metabolites and pharmacology among these potential substitutes.MethodsSix botanical samples were analyzed via LC-MS/MS for metabolite profiling and phenolic quantification. Pharmacological comparisons employed LPS-stimulated RAW264.7/MC3T3-E1 and MH7A cell models. Mechanistic studies on macrophage polarization (LPS/IL-4-induced RAW264.7), osteoblast mineralization, and synoviocyte behaviors (proliferation/migration/invasion) were conducted for top candidates.ResultsA total of 54 metabolites were identified in the samples by LC-MS/MS. Pse showed the highest metabolite similarity to Esc, and both Pse and Psh.V contained higher levels of phenolic compounds than Esc. Combined with the pharmacodynamic results, Pse was superior Psh.V in anti-RA efficacy and was the only comparable potential substitute. Mechanistically, both Esc and Pse: Modulated M1/M2 macrophage polarization; Enhanced osteogenic markers (Runx2, Osx, Ocn) and mineralization; Inhibited synoviocyte proliferation/migration/invasion via Bcl-2 suppression and Caspase-3 activation.ConclusionMultidimensional analysis confirmed that Pse is the optimal potential substitute for Esc, with high similarity in both metabolites and biological activities between the two. Both botanical medicines can slow the progression of RA by regulating immune responses, stimulating osteoblast differentiation, and inducing synoviocyte apoptosis. This study provides critical evidence for the sustainable utilization of Esc resources and expands treatment options for RA.